2019
DOI: 10.1093/ee/nvz070
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Physiological Resistance to Desiccation in Spotted Wing Drosophila (Diptera: Drosophilidae)

Abstract: With a high surface to volume ratio, small organisms must carefully regulate their internal water status. Spotted-wing drosophila, Drosophila suzukii (Matsumura), is an invasive frugivorous insect distributed across a wide range of geographical regions that can have periods of dry and hot weather, suggesting that this species has strategies to avoid stressful environments and reduce water loss. It also survives winter as an adult fly, indicating that it has adaptations to the low air humidity of this season. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…D. suzukii appears in two morphs, i.e., the summer and the winter morph with distinct ecological traits. The winter morph, for instance, is more robust at low humidity conditions than the summer morph (Toxopeus et al, 2016;Fanning et al, 2019). D. melanogaster as a cosmopolitan species also shows geographical variation (Rajpurohit et al, 2017;Dong et al, 2019).…”
Section: Discussion Desiccationmentioning
confidence: 99%
“…D. suzukii appears in two morphs, i.e., the summer and the winter morph with distinct ecological traits. The winter morph, for instance, is more robust at low humidity conditions than the summer morph (Toxopeus et al, 2016;Fanning et al, 2019). D. melanogaster as a cosmopolitan species also shows geographical variation (Rajpurohit et al, 2017;Dong et al, 2019).…”
Section: Discussion Desiccationmentioning
confidence: 99%
“…Nevertheless, we would still expect that a large portion of water is lost via the cuticle during desiccation stress in live insects. Studies have shown that cuticular transpiration is largely passive ( Hadley et al, 1986 ) and accounts for >80% of the water loss during desiccation events ( Gibbs et al, 1998 , 2004 ; Fanning et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, insects show a remarkable ability to maintain water balance using an arsenal of behavioral, morphological and physiological adaptations ( Chown et al, 2011 ). These adaptations involve mechanisms to acquire water, and to reduce or tolerate water loss, thereby enabling insects to subsist in dry and hot environments ( Sheikh et al, 2017 ; Fanning et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the Sonoran Desert (Arizona, USA), for example, adult flies choose cooler and moist microhabitats such as necrotic cacti (Gibbs, 2002 b ). In the laboratory, D. suzukii flies preferred a moist environment when the air humidity difference between the conditions offered was at least 25% (Fanning et al ., 2019). D. melanogaster adults also rapidly move to moist locations in both natural environments and under laboratory conditions (Sun et al ., 2018).…”
Section: Constraints Of Drosophila Desiccation Resistancementioning
confidence: 99%